PENGGUNAAN PERMAINAN UNO CARD SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA SMA NEGERI 2 PEKANBARU Rahmita Putri Hamidah*, Rasmiwetti **, Be - Rahmita Putri Hamidah; Rasmiwetti Rasmiwetti; Betty holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to increase students achievement by use of unocard games as a chemo-edutainment media on learning topic of colloid in XI MIASMAN 2 Pekanbaru. The type of this research is experimental research withrandomized control group pretest-posttest design. Subject of this research are XI MIA 4as the experimental class, XI MIA 3 as the control class which were determinedrandomly after conducting normality and homogeneity test. The experimental groupwas treated with the use of uno card games while the control group without the use ofuno card games. The data analysis to test the hypothesis was using t-test right side.Based on the data analysis, it is obtaine tcount = 2,10 and ttable = 1,66 with α=0,05, dk =77, tcount > ttable is 2,10 > 1,66, It’s mean that use of uno card games as a chemoedutainmentmedia can improve students achievement on the subject of colloid in XIMIA SMA Negeri 2 Pekanbaru. The influence by use of uno card games as a chemoedutainmentmedia to improvement of the student achievement as high as 5,4%.Keywords: Game Uno Card, Learning Achievement.